The Shariah approach to criminalise identity theft - Mohamed, Sidi Mohamed Ould; Zulhuda, Sonny (2014)
Identity theft is one of the crimes that threaten both society and its individuals. Millions of people have been badly affected by identity theft following misuse of their identities by criminals. The term „identity theft‟ is used to include all illicit activities (gathering, utilizing, buying selling, etc.) that target personal information (including natural and legal persons). Identity theft is not a new crime but it has grown and has become a major concern in the era of information. Around the globe, laws and regulations have been enacted and revised to accommodate the phenomenon. Being a divine and timeless law that applies to all matters regardless of their time and location, the Shariah has its own solution to a matter such as identity theft. This paper attempts to define the term „identity theft‟ and then to collect and examine some of the Shariah laws related to crime in general and discuss their applicability to this insurmountable matter (identity theft) in a bit to point out the solution provided by the Shariah to curb terrifying matters such as identity theft which has become a household concern. Furthermore, it is also argued that a study such this will positively contribute to the field of justice as it looks at identity crime from another approach and suggests workable steps that could help to alleviate identity theft.